Effect of Tertiary Preventive Behavior on HbA1c Level, Quality of Life, and Complication Risk in Diabetes Mellitus Patients - Wardhatul Livia; Bhisma Murti; Didik Gunawan Tamtomo; Hanung Prasetya (Journal of Epidemiology and Public Health, 2024)
Background: Type 2 diabetes mellitus (DM) is a non-communicable disease which is a source of additional severity for other diseases. This study aims to determine the effect of tertiary preventive behavior on hba1c level, quality of life (QoL), and complication risk in diabetes mellitus patients.Subjects and Method: This was a cross-sectional study conducted in Sukoharjo, Central Java, Indonesia, from October to November 2023. A total sample of 200 patients with type 2 diabetes mellitus (DM), registered in the Prolanis program, was selected through multistage random sampling. The independent variables were HbA1c levels, risk of complications, and QoL. The inde-pendent variable was tertiary preventive behavior. HbA1c levels were measured using spectrophotometer. QoL was measured using the WHOQOL questionnaire, and risk of complications using a questionnaire. Data were analyzed using the SEM model.Results: Tertiary prevention behavior significantly increased HbA1c level (b= 0.31; CI 95%= -0.45 to 0.15; p<0.001) and quality of life (b= 0.15; 95% CI= -0.15 to 0.38; p<0.001). Tertiary prevention behavior significantly reduced the risk of complications (b= -0.22; CI 95%= -0.42 to 0.02; p= 0.026). The goodness-of-fit values suggest that the structural equation model (SEM) is acceptable (p= 0.188; RMSEA=0.04; CFI=0.97, TLI=0.95; SRMR=0.05; CD= 0.07).Conclusion: Tertiary prevention behavior significantly increased HbA1c level and quality of life. Tertiary prevention behavior reduces the risk of complications in type 2 DM patients. Keywords: Diabetes mellitus, HbA1c, complications, quality of life